Midkine: The Who, What, Where, and When of a Promising Neurotrophic Therapy for Perinatal Brain Injury - Ross-Munro, Emily; Kwa, Faith; Kreiner, Jenny; Khore, Madhavi; Miller, Suzanne L.; Tolcos, Mary; Fleiss, Bobbi; Walker, David W. (Frontiers in Neurology, 2020)
Midkine (MK) is a small secreted heparin-binding protein highly expressed during embryonic/foetal development which, through interactions with multiple cell surface receptors promotes growth through effects on cell proliferation, migration and differentiation. MK is upregulated in the adult central nervous system after multiple types of experimental injury and has neuroprotective and neuroregenerative properties. The potential for MK as a therapy for developmental brain injury is largely unknown. This review discusses what is known of MK’s expression and actions in the developing brain, areas for future research, and the potential for using MK as a therapeutic agent to ameliorate the effects of brain damage caused by insults such as birth-related hypoxia and inflammation.